Quantity of Vaccine Poliovirus Shed Determines the Titer of the Serum Neutralizing Antibody Response in Indian Children Who Received Oral Vaccine - Giri, Sidhartha (J Infect Dis, 2018)
Replication of oral poliovirus vaccine (OPV) in the intestine (ie, vaccine take) is associated with seroconversion and protection against poliomyelitis. We used quantitative polymerase chain reaction analysis to measure vaccine shedding in 300 seronegative infants aged 6–11 months and in 218 children aged 1–4 years 7 days after administration of monovalent or bivalent OPV. We found that the quantity of shedding correlated with the magnitude of the serum neutralizing antibody response measured 21 or 28 days after vaccination. This suggests that the immune response to OPV is on a continuum, rather than an all-or-nothing phenomenon, that depends on efficient vaccine virus replication.